Radium isotopes assess water mixing processes and its application in the Zhujiang River estuary - 郭肖伊 许博超 于志刚 李秀芹 南海明 简慧敏 江雪艳 刁少波 高茂生 (Chinese journal of oceanology and limnology, 2017)
Radium （Ra） isotopes are useful for tracing water mass transport and examining estuarine hydrological dynamics. In this study, several hydrological parameters, nutrients, ehlorophyll-a （ehl-a）, suspended particulate matter （SPM） and Ra isotopes （223Ra, 224Ra and 226Ra） of surface waters of the Zhujiang （Pearl） River estuary （ZRE） were measured. This was done for both winter （December） and summer （July） seasons, to quantitatively understand the seasonal characteristics of river plume flow rate and trajectories, as well as the ecological response. The results show that Ra concentrations in summer were higher than in winter, especially Z24Ra （about 2-5 times higher）. The spatial distribution of three Ra isotopes and relative Ra water ages indicated that river water mainly flushed out of ZRE through the western side in winter, where the water transport was about 5 days faster than in the eastern zone. In summer, diluted river water expended to the east side, resulting in fairly similar water ages for both sides of the river mouth. Although nutrients were higher during the summer season, lower chl-a concentrations indicated that reduced primary production might be caused by high SPM （low light penetration）. The results obtained from this study will provide knowledge needed for effectively developing and managing the ZRE.